2006
DOI: 10.1002/pssc.200565191
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high quality GaN‐based light‐emitting diodes grown on alumina‐rich spinel and sapphire substrates

Abstract: High quality GaN-based light-emitting diodes (LEDs) can be achieved on alumina-rich spinel (MgAl 6 O 10 ), a new substrate material with better thermal and lattice match to GaN than sapphire. As alumina-rich spinel is chemically very close to sapphire (Al 2 O 3 ), the GaN metal-organic chemical vapour deposition (MOCVD) conditions developed for c-plane sapphire have been successfully replicated on it. In this article, we report on the electroluminescence (EL) properties of GaN-based LEDs grown by MOCVD simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In addition, the growth temperature of the 1:3 spinel is lower about 100-200 • C than that of MgAl 2 O 4 , which is in favor of crystal growth. Tinjod et al [11] reported that the GaN-based LEDs grown by MOCVD on 1:3 spinel-(1 1 1) exhibit a higher EL-intensity and a narrower EL-linewidth than those grown on Al 2 O 3 . 1:3 spinel is a promising substrate material for GaN epitaxial growth.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the growth temperature of the 1:3 spinel is lower about 100-200 • C than that of MgAl 2 O 4 , which is in favor of crystal growth. Tinjod et al [11] reported that the GaN-based LEDs grown by MOCVD on 1:3 spinel-(1 1 1) exhibit a higher EL-intensity and a narrower EL-linewidth than those grown on Al 2 O 3 . 1:3 spinel is a promising substrate material for GaN epitaxial growth.…”
Section: Introductionmentioning
confidence: 98%